2021
DOI: 10.9756/int-jecse/v13i2.211092
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Parents with (ADHD) towards the Most Prominent Challenges of Distance Learning in Light of the Covid-19 Pandemic

Abstract: The study seeks to understand and reflect upon the attitudes of the parents of ADHD diagnosed children concerning the most predominant challenges of distance learning during isolation in the Covid 19 pandemic. To achieve this goal, the researchers conducted a descriptive study using an electronic survey on a sample of 28 parents of citizens and residents in the Emirate of Abu Dhabi / United Arab Emirates. The attitudes of parents of students with special needs towards the most prominent challenges of distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In other studies, parents of children with ADHD stated that there were not enough academic accommodations (Becker et al;Ellala et al, 2021;Termine et al, 2021). They also reported stress associated with greater engagement during remote learning, insufficient teaching accommodations, and a lack of attention in children (Becker et al, 2021;Yousef et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…In other studies, parents of children with ADHD stated that there were not enough academic accommodations (Becker et al;Ellala et al, 2021;Termine et al, 2021). They also reported stress associated with greater engagement during remote learning, insufficient teaching accommodations, and a lack of attention in children (Becker et al, 2021;Yousef et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Because ADHD symptomology is known to impact social, academic, and adaptive functioning during typical circumstances, it follows that ADHD symptomology would also have an impact on behavior during virtual learning during the pandemic. Recent studies from outside of the U.S. report that during the pandemic, children with ADHD ranging from four to 15 years old had a harder time with virtual learning than their typically developing peers based on parent surveys, interviews, and behavior rating scales (Ellala, AL‐Tkhayneh, & Abu‐Attiyeh, 2021 ; Tessarollo et al, 2021 ). Specifically, Tessarollo et al ( 2021 ) found that reports of independence during virtual learning was significantly lower for parents of children with ADHD compared to ratings of typically developing children.…”
mentioning
confidence: 99%